2012
DOI: 10.1371/journal.pone.0043512
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2-Dependent Dendritic Cell Death, Maturation, and Priming of T Cells in Response to Brucella abortus Infection

Abstract: Smooth virulent Brucella abortus strain 2308 (S2308) causes zoonotic brucellosis in cattle and humans. Rough B. abortus strain RB51, derived from S2308, is a live attenuated cattle vaccine strain licensed in the USA and many other countries. Our previous report indicated that RB51, but not S2308, induces a caspase-2-dependent apoptotic and necrotic macrophage cell death. Dendritic cells (DCs) are professional antigen presenting cells critical for bridging innate and adaptive immune responses. In contrast to Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Disruption of the rfbE or rfbD gene induces the transformation of smooth-type Brucella strains into rough-type strains due to the creation of an incomplete LPS lacking O-antigen (19). The ⌬rfbE mutant shows a rough phenotype, which enhances internalization into the host cell and induces macrophage oncosis and necrosis, like the case with other Brucella rough mutants (29,34,35). The mutant also has reduced survival in the host cell and fails to establish chronic infection in a mouse model (23).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the rfbE or rfbD gene induces the transformation of smooth-type Brucella strains into rough-type strains due to the creation of an incomplete LPS lacking O-antigen (19). The ⌬rfbE mutant shows a rough phenotype, which enhances internalization into the host cell and induces macrophage oncosis and necrosis, like the case with other Brucella rough mutants (29,34,35). The mutant also has reduced survival in the host cell and fails to establish chronic infection in a mouse model (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cattle DCs are resistant to B. abortus infection, in spite of exhibiting some signs of maturational and activation impairment and lack of up-regulation of co-stimulatory molecules and IL-12p40 after infection [37]. Mice and human DCs are susceptible to B. abortus infection [36,38]. These differences in susceptibility of DCs among hosts may be related to the differences observed in the progression of the disease, since cattle is more able to control the infection, showing less clinical signs compared to humans and some mice strains.…”
Section: Cellsmentioning
confidence: 99%
“…These differences in susceptibility of DCs among hosts may be related to the differences observed in the progression of the disease, since cattle is more able to control the infection, showing less clinical signs compared to humans and some mice strains. However, rough B. abortus strains are able to induce higher phenotypic and functional maturation of human and murine DC cells, characterized by IL-12 and TNF-␣ secretion, and naive CD4 T-lymphocytes stimulation, compared to smooth strains [38][39][40]. Higher exposition of outer membrane proteins (Omp) in rough strains, compared to smooth strains, has been indicated as responsible for the stronger DC maturation in infection by rough strains [39].…”
Section: Cellsmentioning
confidence: 99%
See 2 more Smart Citations